Effect of Capital, Education Level, Raw Materials and Length of Business on Production Value and GDP of the Furniture Industry Sector in Palangka Raya City - Hetty Prowita (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2020)
This study aims to determine the direct effect of capital, level of education, raw materials, and length of business on production value and the indirect effect of capital, level of education, raw materials, and length of business on GRDP of the industrial sector through the value of furniture production in the city of Palangka Raya. This type of research is descriptive quantitative research method using Path Analysis (Analysis Path). The results showed that the variables of capital, education level, raw materials directly and significantly affect the value of furniture production in the city of Palangka Raya. The variable level of education directly and significantly affects the GRDP of the industrial sector, while capital, raw materials, length of business, and production value have no significant effect on the GRDP of the industrial sector. The variables of capital, education level, raw materials, and length of business indirectly have no significant effect on the GRDP of the industrial sector through the value of furniture production in the city of Palangka Raya.